(untitled) (Journal of Contemporary Philology, 2019)
Mythic and historical memory are two sides of the same reality. Popular legends remind us that there are great tragedies behind great epic heroes and mythic feats. Hidden behind the great works of culture lie shocking human and national stories. The collective memory of the Macedonians is sensitive and, apart from the ability to idealize, it can also demystify historical figures and accounts. Macedonian pop-ular tradition keeps numerous legends, stories and poems which evoke the motif of sacrifice, both in its archaic ritual form (burying a live woman in the foundations of bridges) and in its feudal forms of social and cultural politics. The focus of this paper will be on the legends of King Marko (1335-1395) and Marko’s Towers written by Marko Cepenkov (1829-1920). This text will make a basic classification of violence (necessary versus unnecessary violence).